Kritik atas Determinisme dalam Model Transisi Demokrasi - Sriyanto, Nanto (Pusat Penelitian Politik, 2005)
Democratization has spilled over to many new transitional countries. Democratization is a model firstly stated by Rustow in 1970’s to distinguish it from democracy. The Model assumes that genesis andfunction of democracy is different. The model emphasizes dynamic role of strategic actors or elite topromote democratization through bargaining process. Since then, the model has been modified with some ad hoc argument takenfrom new evidences. Since the model only give emphasize to dynamic role of strategic actors, it has produce deterministic conclusion. The determinism ofthe model is caused by disregard of structural and non-political factor. Ifthe model is deterministic, can the liberal democracy that taken as ideal purpose ofdemocratic transition unbounded from determinism ofthe model? Is there another model of democracy that contains local aspect ofmany transition States?